Leaf shape and size track habitat transitions across forest–grassland boundaries in the grass family (Poaceae). (26th March 2019) - Gallaher, Timothy J.; Adams, Dean C.; Attigala, Lakshmi; Burke, Sean V.; Craine, Joseph M.; Duvall, Melvin R.; Klahs, Phillip C.; Sherratt, Emma; Wysocki, William P.; Clark, Lynn G.
Abstract: Grass leaf shape is a strong indicator of their habitat with linear leaves predominating in open areas and ovate leaves distinguishing forest‐associated grasses. This pattern among extant species suggests that ancestral shifts between forest and open habitats may have coincided with changes in leaf shape or size. We tested relationships between habitat, climate, photosynthetic pathway, and leaf shape and size in a phylogenetic framework to evaluate drivers of leaf shape and size variation over the evolutionary history of the family. We also estimated the ancestral habitat of Poaceae and tested whether forest margins served as transitional zones for shifts between forests and grasslands. We found that grass leaf shape is converging toward different shape optima in the forest understory, forest margins, and open habitats. Leaf size also varies with habitat. Grasses have smaller leaves in open and drier areas, and in areas with high solar irradiance. Direct transitions between linear and ovate leaves are rare as are direct shifts between forest and open habitats. The most likely ancestral habitat of the family was the forest understory and forest margins along with an intermediate leaf shape served as important transitional habitat and morphology, respectively, for subsequent shifts across forest–grassland biome boundaries.